Marketing of Titanium Dioxide by Kerala Minerals and Metals Limited - An Analysis - Boniface, P. J.; Sakeer Husain, A.; Bijukumar, S. (Indian Journal of Marketing, 2011)
The Kerala Minerals and Metals Ltd. is exporting Titanium Dioxide (Rutile) to different countries in the world like China, Sri Lanka, South Korea, Italy, Turkey, Bahrain, Iran, Singapore and South Africa. The K.M.M.L. is facing stiff competition from the giant multinational companies like El Dupont de Nemourous and Co. Inc. - U.S.A., Kerr-McGee Chemical Corporation - U.S.A., Kronos Titan - Germany, Ishiharo Sangyo Karsha - Japan, Sachtleben - Germany, National Titanium Dioxide Company - Saudi Arabia, Kemira - Finland, Huntsman Tioxide - a joint venture between Huntsman and ICIPIC and Woodall - U.S.A. are also involved in the marketing of Titanium Dioxide. The K.M.M.L. also produces Titanium Tetra Chloride, Monazite, Ilmenite Zircon and Rutile. The major product of KMML is Titanium Dioxide (Rutile) (TiO2), in which the company enjoys monopoly in India. It is worthwhile to know how far K.M.M.L. has succeeded in marketing their products by competing with the multinational companies. The objective of the study is to analyze the trends in the marketing of the products of Kerala Minerals and Metals Ltd.